Efficacy and Safety of HIFU in Improving Bladder Control in Women with Urinary Incontinence - Sampana Fatima; Aqsa Saleem; Sana Rauf; Shagufta Awais; Sadia Kanwal; Wajeeha Imam (Proceedings)
Introduction: Urinary incontinence is a common gynecological issue, affecting millions of women worldwide due to the weakening of pelvic floor muscles.